APPLICABILITY OF DIRECT EVAPORATIVE COOLING FOR LOW-RISE RESIDENTIAL BUILDING IN SURABAYA - I Gusti Ngurah Antaryama (DIMENSI (Journal of Architecture and Built Environment), 2022)
Direct evaporative cooling has been widely known as the passive design strategy for ameliorating the thermal conditions of building in hot-dry climates. In the recent past, the strategy has been extended to warm-humid climates. The scope varies from exploring the system to applying the method to buildings. Few studies have been conducted regarding its application on a multi-story residential building. In response to this gap, the present study will explore the strategy's applicability on the typical low-rise housing in Surabaya and analyze its environmental consequences. Simulation is used as the primary method for the analyses. Results of the study show that direct evaporative cooling is applicable in warm-humid tropics, but with some notes regarding the increase of air humidity. Dimensional properties of the cooling pad can be arranged to minimize the increased humidity.